Nature of the doubly-charmed tetraquark Tcc+ in a constituent quark model - P.G. Ortega; J. Segovia; D.R. Entem; F. Fernández (Physics Letters B, 2023)
The recently discovered Tcc+ is evaluated as a DD⁎ molecular structure in the JP=1+ sector. A coupled-channels calculation in charged basis, considering the D0D⁎+, D+D⁎0 and D⁎0D⁎+ channels, is done in the framework of a constituent quark model that successfully described other molecular candidates in the charmonium spectrum such as the X(3872). The Tcc+ is found as a D0D⁎+ molecule (87%) with a binding energy of 387 keV/c2 and a width of 81 keV, in agreement with the experimental measurements. The quark content of the state forces the inclusion of exchange diagrams to treat indistinguishable quarks between the D mesons, which are found to be essential to bind the molecule. The D0D0π+ line shape, scattering lengths and effective ranges of the molecule are also analyzed, which are found to be in agreement with the LHCb analysis. We search for further partners of the Tcc+ in other charm and bottom sectors, finding different candidates. In particular, in the charm sector we find a shallow JP=1+ D+D⁎0 molecule (83%), dubbed Tcc′, just 1.8 MeV above the Tcc+ state. In the bottom sector, we find an isoscalar and an isovector JP=1+ bottom partners, as BB⁎ molecules lying 21.9 MeV/c2 (I=0) and 10.5 MeV/c2 (I=1), respectively, below the B0B⁎+ threshold.